Effect of the positional relationship between the interference screw and the tendon graft in the bone tunnel in ligament reconstruction. (8th January 2019) - Aoki, Akira; Imade, Shinji; Uchio, Yuji
Purpose: To reveal the effects of the positional and length relationships between the interference screws (ISs) and the tendon graft in the bone tunnel on the fixation strength in ligament reconstruction. Methods: We compared three IS positions on the anterior (the Anterior group) or posterior (the Posterior group) or side (the Side group) of the tendon graft in relation to the pullout direction. The tendon graft was pulled at 0°, 30°, 60°, and 90° to the bone tunnel, and the maximum pullout load at each angle was compared among the groups. We also investigated the relationship between the length of the tendon graft and the length of the IS in the bone tunnel. The direction of the pullout force was the same as that of the Anterior group, and the maximum load was compared between groups in which the tendon graft was longer or shorter than the IS. Results: The maximum loads of the Anterior group were significantly greater than those of the Posterior and Side groups at the traction angles of 30° and 60°, respectively. An IS shorter than the tendon graft was found to provide significantly superior fixation strength compared to an IS longer than the tendon graft. Conclusions: Better fixation strength was achieved when the IS was placed on the side of the anchorage tunnel on which the tendon graft was loaded and the IS was shorter than the tendon graft.